THE IMPACT OF IMPLEMENTING NUMBERED HEADS TOGETHER COOPERATIVE LEARNING MODEL ON THE COMMUNICATION SKILL OF STUDENT AT JUNIOR HIGH SCHOOL 3 TEBO - Mawarni Sulistianingsih; Firda Az Zahra; Skunda Diliarosta; Rahmah Evita Putri (UNIVERSITAS NEGERI MEDAN, 2024)
Low student communication skills have been the cause of this research, which had an impact on learning outcomes because there had not been training on students' communication skills through the application of appropriate learning models. The learning process, which still uses conventional learning models, namely group discussions, has not made each student active and responsible for group assignments and has not trained communication skills in scientific arguments. Therefore, an appropriate learning model is needed, one of which is the Numbered Head Together (NHT) type cooperative learning model. The aim of the research is to determine the effect of implementing the NHT type cooperative learning model on the communication skills of SMPN 3 Tebo students. The research uses a Quasi-Experimental type of research with a Nonequivalent Control Group Design. The research began with a pretest in the experimental class and control class, then treatment was given to the experimental class, and at the end of the learning process, a posttest was given to both classes. Samples were taken using purposive sampling technique. The test instrument consists of 13 description questions. Data were analyzed using Microsoft Excel to carry out prerequisite tests and hypothesis tests on overall communication skills and each ability indicator. The results of the research showed that there was an increase in students' overall communication skills between before and after treatment. Through the Mann Whitney test with Zcount -5.32 and Ztabel 1.96 with the criterion that H0 is accepted if –Ztabel ≤ Zcount ≤ Ztabel, then Zcount -5.32 < -Ztabel -1.96, then H0 is rejected, and H1 is accepted. It can be concluded that there is a significant influence of implementing the Numbered Head Together type learning model on the communication skills of students at SMP Negeri 3 Tebo Regency.